Strategi Pengembangan Kawasan Agroindustri Terintegrasi yang Berbasis Ekspor di Provinsi Jambi - Syurya Hidayat; Yohanes Vyn Amzar (EKO-REGIONAL, 2007)
This research is purposed to identify some agro industry regions where the potencies can be developed integrated by export basis and to make abbreviation strategy to improve it. It is focused in Jambi Province. This research identify there are four integrated export basis regional areas in Jambi. There are KATE; Sarolangun, Tanjab barat, Tanjab Timur and Muara Jambi. To develop integrated agro industry export basis area In Jambi, five important strategies should be existed; (1) focus on riel leading or superior export product, (2) linkage with other industry, (3) linkage with other agro industry region, (4) market clear policy, and (5) the important rule of government that facilitate economic development.Key words: export basis, KATE, integrated export